Effects of footwear on plantar foot sensitivity are frequency dependent: A study with Formula 1 footwear - Schlee, G.; Sterzing, T.; Milani, T. L. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
The sensory function of the human foot allows the perception of different mechanical stimuli. These stimuli provide important sensory information, which are used for the fine regulation of movements. Through mechanoreceptors located in the skin, the foot is able to recognize different stimuli such as touch and vibration. Studies have shown that foot vibration sensitivity of healthy subjects is influenced by age (Inglis et al., 2002), foot region (Sterzing et al., 2006), and vibration frequency (Nurse & Nigg, 1999). Furthermore, clinical studies have shown that diseases of the Central Nervous System, e. g. Diabetes and Morbus Parkinson, have negative effects on vibration sensitivity of the plantar foot (Dyck et al., 1987; Prätorius & Milani, 2004). Foot sensitivity is also important for sports performance. Schlee et al. (2007) showed that gymnasts have better mean foot vibration sensitivity than volleyball players. They concluded that technical demands of the sport as well as footwear usage during practice and competition may influence the vibration sensitivity of athletes. Effects of footwear on plantar foot vibration sensitivity need to be investigated, since most of the studies involving foot sensitivity are performed barefoot. Additionally, according to Formula 1 drivers, their footwear must provide "pedal feeling", which is very important for driving performance. Therefore, the objective of this research is to investigate the effects of Formula 1 footwear on plantar foot vibration sensitivity.